HYSYS: an introduction to chemical engineering simulation for UTM Degree++ program - Abd Hamid, Mohd. Kamaruddin (Universiti Teknologi Malaysia, 2007)
HYSYS is a powerful engineering simulation tool, has been uniquely created with respect to the program architecture, interface design, engineering capabilities, and interactive operation. The integrated steady state and dynamic modeling capabilities, where the same model can be evaluated from either perspective with full sharing of process information, represent a significant advancement in the engineering software industry. The various components that comprise HYSYS provide an extremely powerful approach to steady state modeling. At a fundamental level, the comprehensive selection of operations and property methods allows you to model a wide range of processes with confidence. Perhaps even more important is how the HYSYS approach to modeling maximizes your return on simulation time through increased process understanding. To comprehend why HYSYS is such a powerful engineering simulation tool, you need look no further than its strong thermodynamic foundation. The inherent flexibility contributed through its design, combined with the unparalleled accuracy and robustness provided by its property package calculations leads to the presentation of a more realistic model. HYSYS is widely used in universities and colleges in introductory and advanced courses especially in chemical engineering. In industry the software is used in research, development, modeling and design. HYSYS serves as the engineering platform for modeling processes from Upsteam, through Gas Processing and Cryogenic facilities, to Refining and Chemicals processes. There are several key aspects of HYSYS which have been designed specifically to maximize the engineer’s efficiency in using simulation technology. Usability and efficiency are two obvious attributes, which HYSYS has and continues to excel at. The single model concept is key not only to the individual engineer’s efficiency, but to the efficiency of an organization. Books about HYSYS are sometimes difficult to find. HYSYS has been used for research and development in universities and colleges for many years. In the last few years, however, HYSYS is being introduced to universities and colleges students as the first (and sometimes the only) computer simulator they learn. For these students there is a need for a book that teaches HYSYS assuming no prior experience in computer simulation.